IMPLEMENTASI METODE MOORA DALAM PENGAMBILAN KEPUTUSAN PENENTUAN LOKASI TERBAIK UNTUK MINYAK SAWIT BERKUALITAS PADA KUD KARYA MUKTI BERBASIS WEB - Titis Wulandari; Siti Fathuroh; Tri Wera Agrita (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2020)
Oil palm is the main ingredient in producing oil products, to produce palm oil which is needed for a strategic location and good soil conditions. Especially in the development of the company in order to update the development system to improve the quality of work of the company. The study was aimed to assist in making decisions for determining the best location to produce quality palm oil. in this study processing was carried out in the form of soil location, soil conditions and other supporting data obtained from interviews. Interviews were conducted with the KUD Karya Mukti Bungo Districts. this study were tested using 10 soil data that has been submitted and 6 assessment criteria. The study was analyzed using the method Multi-Objective Optimization on The Basic of Ratio Analysist (MOORA). The MOORA method will process soil data to produce the optimal value from the assessment criteria for each soil data. Based on the results of testing using the MOORA method, it was found that the results rank for the optimal value of each soil with the highest value were 7.56. Then this method can be implemented to determine the location of the oil palm so as to produce the best decision.